Viable Intrauterine Pregnancy and Coexisting Molar Pregnancy in a Bicornuate Uterus: A Rare Presentation - Krishnamoorthy, Kavitha (J Clin Imaging Sci, 2016)
A complete hydatidiform mole with a viable coexisting fetus (CMCF) is a rare occurrence. Similarly, Mullerian anomalies such as a bicornuate uterus are uncommon variants of normal anatomy. We report a case of a 40-year-old female with a known bicornuate uterus presenting at 13 weeks gestation with vaginal bleeding. Ultrasound findings showed a healthy viable pregnancy in the right horn with complete molar pregnancy in the left horn. After extensive counseling, the patient desired conservative management, however, was unable to continue due to profuse vaginal bleeding. The patient underwent suction dilation and curettage under general anesthesia and evacuation of the uterine horns. Postoperatively, the patient was followed until serum beta-human chorionic gonadotropin (β-hCG) level dropped to <5 mU. This is the first case of a CMCF reported in a bicornuate uterus, diagnosed with the use of ultrasound imaging.